Meaningful talk - Jorge M. Streb; Gustavo Torrens (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2011)
In economics, the standard approach to language is that talk is cheap. Here, instead, language is a social convention that affects utility. Unless language is used in its ordinary sense, it cannot help to coordinate actions because there is no way of decoding it. This points to a unique informative equilibrium where words are used in their ordinary sense in natural language. Misrepresentation costs may eliminate uninformative, babbling, equilibria. More generally, meaningful talk provides a concrete mechanism through which consistent expectations are generated in Nash equilibria.
Keywords: D8; C7; 330; cheap talk; symbols; meaning; encoding-decoding; common priors; Nash equilibria